(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article delves into the linguistic and cultural analysis of phraseological units (PUs) with onomastic components, focusing on their role in reflecting the national mentality and cultural identity of the English, Russian, and Uzbek languages. The research emphasizes the significant role of onomastics in shaping phraseological expressions, which carry not only linguistic but also historical, cultural, and social meanings. The study outlines various linguistic theories and methodologies, including comparative analysis, to examine how onomastic elements in phraseological units express national characteristics, historical events, and cultural values. It investigates the formation, meaning, and cultural significance of these expressions in different languages and highlights how they contribute to the development of language and culture. The research is rooted in a cross-linguistic approach, providing insights into the comparative study of onomastic phraseology in the aforementioned languages.